The Role of Biomedical Engineering in Dental Health Care in Indonesia - Siswomihardjo, Widowati; Sunarintyas, Siti (2006)
To achieve the vision of Healthy Indonesia 2010, a good health care service throughout the whole Indonesian community is needed, including the service in dental health care. This service covers promotive, preventive, curative, and rehabilitative treatments. The success of all dental health care is very much supported by the presence of dental instrumentations and biomaterials. Since those two components are still imported, makes dental health care quite expensive, and this is the reason why the implementation of dental health care service in Indonesia is not well spread yet. Since biomedical engineering is an interdisciplinary study between medical and engineering, therefore the big challenge of dental health care in Indonesia will be solved by biomedical engineering.